2017
DOI: 10.1371/journal.pone.0169713
|View full text |Cite
|
Sign up to set email alerts
|

Does Measles Vaccination Reduce the Risk of Acute Respiratory Infection (ARI) and Diarrhea in Children: A Multi-Country Study?

Abstract: BackgroundPneumonia and diarrhea occur either as complications or secondary infections in measles affected children. So, the integrated Global Action Plan for Pneumonia and Diarrhea (GAPPD) by WHO and UNICEF includes measles vaccination as preventive measure in children. The objective of the study is to examine the effect of measles vaccination on Acute Respiratory Infection (ARI) and diarrhea in children in the Democratic Republic of Congo, Ethiopia, India, Nigeria, and Pakistan.MethodsWe analyzed data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
3
26
1
2
Order By: Relevance
“…The mothers of these children were negligent in preserving immunization cards and hence we feel that among these children the immunization status may not be as high as 94.6%. In a Demographic and Health Surveys (DHS) done in the Republic of Congo, Ethiopia, India, and Pakistan found that Children who were given the measles vaccine were less likely to suffer from ARI than unvaccinated children in India and Pakistan [ 24 ]. In the current study, Pneumonia was reported to be higher in a partially immunized child than in fully immunized children.…”
Section: Discussionmentioning
confidence: 99%
“…The mothers of these children were negligent in preserving immunization cards and hence we feel that among these children the immunization status may not be as high as 94.6%. In a Demographic and Health Surveys (DHS) done in the Republic of Congo, Ethiopia, India, and Pakistan found that Children who were given the measles vaccine were less likely to suffer from ARI than unvaccinated children in India and Pakistan [ 24 ]. In the current study, Pneumonia was reported to be higher in a partially immunized child than in fully immunized children.…”
Section: Discussionmentioning
confidence: 99%
“…The control variables included in the analysis of (risk of) occurrence of bloody diarrhea are ‘initiation of breastfeeding (within 1 hour, within 1–24 hours, after 24 hours) [27], bottle feeding (yes, no), age of child (below 12 months, 12–23, 24–35, 36–47, 48–59 months) [7], sex of child (male, female), size of child at birth (smaller than average, average and larger) [23]. The analysis also includes literacy of mother (literate, non-literate) [7], exposure to mass media (exposed, unexposed) [28], religion (Hindu, other) [23], caste/tribe (Scheduled Caste (SC) and Scheduled Tribe (ST), other) [29], household wealth status (poor, middle, rich) [28], and place of residence (urban, rural) [7] as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…This infers that the MCV1 vaccination has a negative correlation with the malnutrition status of the children. We also found that, the children who had not received MCV1 were more likely to suffer from fever, diarrhea, anaemia and malnutrition [ 39 ]. A distinct social gradient permeates India’s measles vaccination coverage, with children of parents with higher education and wealth more likely to be vaccinated with MCV1 compared with children born to socio-economically vulnerable mothers.…”
Section: Discussionmentioning
confidence: 99%